FACTORS AFFECTING THE ROLE OF NURSES IN MEDICATION SAFETY: A LITERATURE REVIEW - Lalujan, Fanda; Musharyanti, Lisa (Universitas Respati Yogyakarta, 2021)
Mistakes during medical treatments are a rising concern in patient safety. Nurses are critical in ensuring the safe administration of drugs to patients, influenced by various factors. This literature review aims to identify factors influencing nurses in medication safety. The pieces of literature were sourced from the PubMed, Proquest, Science-Direct, and Willey Library electronic databases, with search terms of â€œrisk factor or related factorâ€, â€œnurse or nurse role,â€ â€œmedication errorâ€, â€œdrug safetyâ€, â€œdrug administrationâ€. The review process resulted in twenty-three original articles meeting the inclusion criteria. The review shows five main factors influencing a nurseâ€™s role in medication safety which are; organization & management (training programs, career paths, medication error reporting systems, staffing, information systems), working environment (additional routines, official shifts, number of service days, interruptions during action, workloads), work, learning culture), team (leadership style, oral and written communication), nurseâ€™s personal and work history (age, length of work, experience, education, knowledge and skills/competence, motivation and attitude, nurse awareness) and task (availability & use of protocol). Keywords: Nurseâ€™s Role; Medication Errors; Patient Safety; Medication System